High-Performance Energy Storage and Conversion Materials Derived from a Single Metal–Organic Framework/Graphene Aerogel Composite - Xia, Wei; Qu, Chong; Liang, Zibin; Zhao, Bote; Dai, Shuge; Qiu, Bin; Jiao, Yang; Zhang, Qiaobao; Huang, Xinyu; Guo, Wenhan; Dang, Dai; Zou, Ruqiang; et al. (Nano letters, 2017)
Metal oxides and carbon-based materials are the most promising electrode materials for a wide range of low-cost and highly efficient energy storage and conversion devices. Creating unique nanostructures of metal oxides and carbon materials is imperative to the development of a new generation of electrodes with high energy and power density. Here we report our findings in the development of a novel graphene aerogel assisted method for preparation of metal oxide nanoparticles (NPs) derived from bulk MOFs (Co-based MOF, Co(mIM)2 (mIM = 2-methylimidazole). The presence of cobalt oxide (CoO x ) hollow NPs with a uniform size of 35 nm monodispersed in N-doped graphene aerogels (NG-A) was confirmed by microscopic analyses. The evolved structure (denoted as CoO x /NG-A) served as a robust Pt-free electrocatalyst with excellent activity for the oxygen reduction reaction (ORR) in an alkaline electrolyte solution. In addition, when Co was removed, the resulting nitrogen-rich porous carbon–graphene composite electrode (denoted as C/NG-A) displayed exceptional capacitance and rate capability in a supercapacitor. Further, this method is readily applicable to creation of functional metal oxide hollow nanoparticles on the surface of other carbon materials such as graphene and carbon nanotubes, providing a good opportunity to tune their physical or chemical activities.